A classification of specific movement skills and patterns during sprinting in English Premier League soccer - Caldbeck, P, Dos´Santos, T. (PLOS ONE, 2022)
The aim of this study was to quantify and contextualize sprinting actions (= 7.0 m/s) of English Premier League (EPL) soccer match-play with respect to the movement skills and patterns employed. Video footage (3.2.6, Premier League DVMS, ChyronHego) and raw video-based locomotor coordinates of 901 sprint efforts from 10 matches of an EPL soccer team (2017-2018), were evaluated using the Football Sprint Movement Classification System pertaining to transition, initiation, and actualisation of sprint movement skills and patterns. The results from a one-way ANOVA or independent t-test revealed that, generally, most sprinting actions begun from a linear initiation position compared to lateral or rear (63%, d = 5.0-5.3, p < 0.01), without a change of direction (COD) (48%, d = 4.9-5.6, p < 0.01) compared to lateral, front-back, back-front, and from forward travelling (linear and diagonal) transition movements (68%, d = 2.1-5.7, p < 0.01) compared to lateral or rear. Additionally, most sprints were initiated with a rolling acceleration (66%, d = 3.2, p < 0.01) compared to explosive acceleration, often performed with a degree of curvature (86%, d = 7.2, p < 0.01) compared to linear, with torso rotation (62%, d = 2.7, p < 0.01) compared to no rotation, and typically end with an action such as duelling with an opponent or involvement with the ball (49%). Additionally, the sprint movement characteristics proportions slightly differed across playing positions. Overall, this study confirms that sprints during EPL soccer matches are initiated from and performed with a variety of different movement skills and patterns in relation to different sport-specific outcomes. This data can be used to assist in the development of more effective physical preparation programmes, inform position-specific contextualized sprinting drills to achieve better specificity and potential transfer of training, while also informing speed testing protocols.